Privately Empowered Expressing Feminism in Islam in Northern Nigerian Fiction - Edwin, Shirin (Northwestern University Press, 2016)
Privately Empowered responds to the lack of adequate attention paid to Islam in Africa in comparison to the Middle East and the Arab world. Shirin Edwin points to the embrace between Islam and politics that has limited Islamic feminist discourse to regions where it evolves in tandem with the nation-state and is commonly understood in terms of activism, social affiliations, or struggles for legal reform. Edwin examines the novels of Zaynab Alkali, Abubakar Gimba, and Hauwa Ali due to their emphases on personal engagement, Islamic ritual in the quotidian, and observance of Qur'anic injunctions. Analysis of these texts connects the ways Muslim women in northern Nigeria balance their spiritual habits in ever changing configurations of their private domains. The spiritual universe of African Muslim women may be one where Islam is not the source of their problems or their political activity, but a spiritual activity devoid of political forms.